Can Coasean bargaining justify Pigouvian taxation? - Stephanie Rosenkranz; Patrick W. Schmitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
The fact that according to the celebrated Coase Theorem rational parties always try to exploit all gains from trade is usually taken as an argument against the necessity of government intervention through Pigouvian taxation in order to correct externalities. However, we show that the hold-up problem, which occurs if non-verifiable investments have external effects and parties cannot be prevented from always exploiting ex post gains from trade through Coasean bargaining, may be solved by government intervention. In this sense, the impossibility to rule out Coasean bargaining (after investments are sunk) may in fact justify Pigouvian taxation.
Keywords: L14; H23; H21; D62; 330; Hold-up problem; Bargaining; Contracts; Taxation; Externalities; Coase-Theorem; Internalisierung externer Effekte; Verhandlungstheorie